Des « Fins de L’homme » à la Naissance des Fantômes ou comment prendre la parole ? - Ana Paiva Morais (Carnets)
In this article I argue that the texts of Jacques Derrida, « Les Fins de l’Homme » (1972) and Michel de Certeau, « La prise de parole » (1968) are a key to the understanding of the expression « prise de parole » such as it was used shortly after the events of May 68 in France, and I question the possibility of the use of this expression in more recent times by a short reading of Marie Darrieussecq’s book Naissance des fantômes (1998).